Pengembangan Media Pembelajaran Keterampilan Menyimak Teks Laporan Hasil Observasi dengan Articulate Storyline di SMAN 3 Bantul Tahun Ajaran 2021/2022 - Anik Nurlatifah; Primasari Wahyuni; Fitri Jamilah (LP4MK STKIP PGRI Lubuklinggau, 2021)
The learning media for listening to the text of the observation report that has been used so far is still audio-visual in nature, sourced from Youtube. This makes it difficult for students if they want to learn the previous material so that interesting media is needed and can be studied repeatedly by using articulate storylines. For this reason, the purpose of this study was to describe the results of developing learning media for listening skills to the text of the observation report with an articulate storyline at SMAN 3 Bantul, Academic Year 2021/2022. The research method used was a research and development method with the ADDIE development model. The research was conducted at SMAN 3 Bantul. The subjects used by class X IPS 2 students were 15 students. Data collection techniques using observation, questionnaires, and tests. The results of the study show: 1) this research produces an interactive learning media product, html5 version of articulate storyline and an android application called Indonesian Language Learning Media; 2) the quality of interactive learning media articulate storyline, based on the results of the assessment of media experts by 95% and material experts 92.5%, so it is categorized as very feasible/valid; 3) student interest in articulate storyline learning media by 94% is categorized as very good; and 4) the effectiveness of the articulate storyline media after the trial was carried out, which was 81.64 N gain and categorized as effective.